Rice grain-shaped TiO2–CNT composite—a functional material with a novel morphology for dye-sensitized solar cells - Zhu, Peining (2013)
Titanium dioxide-multiwalled carbon nanotube (denoted as TiO2–CNT) nanocomposites with a novel rice-grains nanostructure are synthesized by electrospinning and subsequent high temperature sintering. The rice grain-shaped TiO2 is single crystalline with a large surface area and the single crystallinity is retained in the TiO2–CNT composite as well. At very low CNT loadings (0.1–0.3 wt% of TiO2), the rice grain shape remains unchanged while at high CNT concentrations (8 wt%), the morphology distorts with CNTs sticking out of the rice-grain shape. The optimum concentration of CNTs in the TiO2 matrix for best performance in dye-sensitized solar cells (DSCs) is found to be 0.2 wt%, which shows a 32% enhancement in the energy conversion efficiency. The electrochemical impedance spectroscopy (EIS) and the incident photon-to-electron conversion efficiency (IPCE) measurements show that the charge transfer and collection are improved by the incorporation of CNTs into the rice grain-shaped TiO2 network. We believe that this facile one-pot method for the synthesis of the rice-grain shaped TiO2–CNT composites with high surface area and single crystallinity offers an attractive means for the mass-scale fabrication of the nanostructures for DSCs since electrospinning is a simple, cost-effective and scalable means for the commercial scale fabrication of one-dimensional nanostructures.